Epidemiology of Q fever in milk by using nested-PCR targeting the repetitive elements IS1111 and COM1 genes in Coxiella burnetii in Iran - Ownagh, A; Mokarizadeh, K; Khademi, P (Journal of the Hellenic Veterinary Medical Society, 2025)
Q fever, which is caused by Coxiella burnetii, distributes worldwide. The main reservoirs of the disease are small ruminants. However, many species of animals can be infected. Humans and animals get Q fever when they breathe in contaminated aerosols accompanied by C. burnetii. The excreted bacterium in the milk could infect animals and humans. In this cross-sectional study, the number 416 cattle milk samples were collected randomly from dairy herds in Khorramabad, Iran in 2019. All the samples were analyzed for the presence of C. burnetii by nPCR targeting two different genes (Trans, Com1). The PCR products were examined by electrophoresis using an agarose gel. All milk samples were subjected to DNA extraction and examined by a high specific nested-PCR method. The frequency of C. burnetii in the evaluated samples using OMP and IS1111 target genes were 24 (5.8%) (95% CI: 3.9%-8.6%), and 60 (14.4%) (95% CI: 11.4%-18.1%) respectively. The results of this study show that Trans-PCR is highly sensitive and useful for the direct detection of C. burnetii in milk samples. This technique is a one-step and fast process in comparison to the other assays. The overall results of this study indicated that cattle milk can be a potential reservoir for C. burnetii in Iran.